COMPARISON BETWEEN HEMODYNAMIC CHANGES OF ATRACURIUM AND CISATRACURIUM IN PATIENTS UNDERGOING CABG SURGERY - Ali, Muhammad; Hussain, Syed Aqeel; Siddiqi, Rashad; Khan, Fahad Ahmad; Javaid, Rehana; Khan, Rahmeen Pervaiz (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the hemodynamic effects of Atracurium versus Cisatracurium in Cardiac Patients Undergoing coronary artery bypass graft Surgery. Study Design: Randomized controlled trial.Place and Duration of Study: The study was conducted at Armed Forces Institute of Rawalpindi, a tertiary care hospital, after seeking hospital ethics committee permission, from Apr 2019 to Oct 2019. Methodology: A total of 200 consecutive patients were randomized into two equal groups, group-A and group-C (100 in each group). Group-A patients were induced with 0.5mg/kg of Atracurium, followed by infusion @ 10μg/kg/min whereas group C patients received Cisatracurium @ 0.2mg/kg at induction, followed by infusion @ 2μg/kg/min during the maintainence phase. Systolic blood pressure, diastolic blood pressure, Mean arterial pressure and heart rate were noted at different intervals of both groups. Decrease in systolic blood pressure of >20% from baseline or a value